Detection of glucose metabolism disorders in coronary patients enrolled in cardiac rehabilitation: Is glycated haemoglobin useful? Data from the prospective REHABDIAB study. (29th August 2020) - Tatulashvili, Sopio; Patois-Vergès, Bénédicte; Nguyen, Amandine; Blonde, Marie-Cécile; Vergès, Bruno
Abstract: Introduction: Diabetes and pre-diabetes are highly prevalent in patients with a history of acute coronary syndrome. This is why screening for glucose metabolism disorders is recommended in patients following an acute coronary syndrome. The aim of our study was to determine whether glycated haemoglobin alone compared with the oral glucose tolerance test could allow effective screening for glucose metabolism disorders in acute coronary syndrome patients undergoing cardiac rehabilitation. Patients and methods: Among 347 patients with a recent history of acute coronary syndrome enrolled in our cardiac rehabilitation centre, 267 patients without previously known diabetes were recruited for this prospective study with performance of both oral glucose tolerance test and glycated haemoglobin measurement. The patients were divided into three groups: newly diagnosed diabetes mellitus, pre-diabetes and normoglycaemia according to the oral glucose tolerance test and glycated haemoglobin results. The results obtained with glycated haemoglobin were compared with those obtained with the oral glucose tolerance test, considered as the reference. Results: For the diagnosis of diabetes, glycated haemoglobin had a sensitivity of 72% and a specificity of 100%. Positive and negative predictive values were high at 100% and 96%, respectively. However, for the diagnosis of pre-diabetes the sensitivity of glycated haemoglobin was low at 64% as were the specificity (53%) and the positive predictive values (37%). Glycated haemoglobin overdiagnosed pre-diabetes (52% vs 30%, p  < 0.0001). For the diagnosis of normoglycaemia, the sensitivity of glycated haemoglobin was also low (48%). Conclusion: According to our study, glycated haemoglobin has low sensitivity and specificity for the detection of pre-diabetes in patients with coronary disease enrolled in cardiac rehabilitation, and glycated haemoglobin over-diagnoses pre-diabetes in comparison with the oral glucose tolerance test.